Protective Effect of Parsley Oil on the Histological Structure of Liver in Adult Mice Induced by Cadmium Chloride - Faten Al-Tai; Maha Abdul Jabar AL-Sammak; H.KH. Isamil (The Indian Veterinary Journal, 2024)
The purpose of the current investigation is  to determine whether parsley oil may mitigate the toxicological effects of cadmium chloride on rat liver cells at the histopathological level. Forty numbers of  mice separated into 4 groups each of 10 animals formed the experimental groups.. The first group served as a control and received distilled water. Cadmium chloride was administered intraperitoneally to the second group at a dose of 3.5 mg/kg, the third group was injected intraperitoneally with cadmium chloride at a dose of 3.5 mg/kg and parsley oil was dosed at a volume of 0.5 ml/kg, the fourth group dosed with parsley oil at a volume of 0.5 ml/kg. For a month, the therapy was administered once daily.  The results of the histopathological assessment of the hepatic tissue in the cadmium chloride treated group revealed generalized blood vessel congestion, diffuse vacuolar degeneration and coagulative necrosis of the hepatocyte and inflammation. The cadmium chloride and parsley oil group showed recovery of hepatocytes to their normal structure, and the central vein was surrounded by hepatocytes similar to the healthy control group This study showed that parsley oil can counteract the toxic effects of cadmium chloride on hepatocytes, which manifest as necrosis and inflammation, and can lessen the toxic consequences of cadmium chloride from a histological perspective.